Psychometric Evaluation of a Novel Instrument Assessing the Impact of Migraine on Physical Functioning: The Migraine Physical Function Impact Diary. Issue 9 (30th August 2017) - Kawata, Ariane K.; Hsieh, Ray; Bender, Randall; Shaffer, Shannon; Revicki, Dennis A.; Bayliss, Martha; Buse, Dawn C.; Desai, Pooja; Sapra, Sandhya; Ortmeier, Brian; Hareendran, Asha
Abstract : Objective: The objective of this study was to evaluate the measurement properties of the Migraine Physical Function Impact Diary (MPFID), a novel patient‐reported outcome (PRO) measure for assessing the impact of migraine on physical functioning. Methods: In a prospective, observational study, adults with episodic migraine (EM) or chronic migraine (CM) used an eDiary to complete the MPFID (assessing daily impacts of migraine on physical function) and a headache diary (capturing migraine days, migraine pain intensity, and migraine interference) each day, and other PRO instruments related to migraine. Item‐level evaluation, item response theory (IRT), and exploratory factor analysis (EFA) methods were applied to identify domains, select final MPFID items, and develop scoring procedures. Psychometric properties of the final 13‐item MPFID were evaluated using confirmatory factor analysis and tests of reliability (Cronbach's α for internal consistency and intra‐class correlation [ICC] for test–retest) and validity (convergent and known‐groups). Results: The study enrolled 569 adults with chronic or episodic migraine, mean (SD) age 39.9 (12.0) years and 87.2% female. Item‐level analyses based on interim data informed selection of a set of 13 items for the MPFID, through evaluation of floor/ceiling effects, item‐to‐item correlations, factor loadings, and IRT‐based fit/misfit statistics. Two domain scores (EA: Impact on Everyday Activities; PI: Physical Impairment) and a global item score for impact on everyday activities were identified. EA and PI domains exhibited high internal consistency ( α  = 0.97; α  = 0.93) and good test–retest reliability among stable subjects (ICCs = 0.74 and 0.77). Convergent validity was demonstrated by moderate correlations ( r  = ±0.50‐0.68; P  < .0001) between MPFID domain scores and number of migraine days, headache days, bed days, and other migraine‐related PRO instruments. EA and PI scores differentiated between groups who varied by number of migraine days, migraine interference levels, migraine pain intensity, and median split groups of scores based on other PROs instruments ( P  < .05). Conclusions: The MPFID has robust psychometric properties (ie, reliability and validity). Findings supported two distinct domains about the impact of migraine on physical functioning: Impact on Everyday Activities and Physical Impairment. Both domain scores showed evidence of excellent reliability and construct validity in assessing the impacts of migraine on physical functioning.